Narrativas (auto)biográficas no documentário brasileiro: do privado ao público - Diógenes, Eliane Vasconcelos (2017)
This research analyzes significance and singularity of the current communication phenomenon in which documentary filmmakers, under the influence either of death trauma or the absence of a person from their family group, aim to recover their stories and their memories through moviemaking. We scrutinize how such intimate, tragic and personal family narratives turn into attractive documentaries that are becoming increasingly prestigious in the audiovisual scene. The first stage of the research consisted in investigating designations and concepts of the documentary with autobiographical narrative. Then, we ascertained about some family stories in the history of documentary cinema, exploring traditions and changes and, subsequently, we examined (auto)biographical narratives in media culture. After that, we analyzed the searching experience for the other through documentary (the interlace between memory and fantasy, mourning preparation and the ethical question between public and private tensions), and at last we explored the aesthetic experiences (creation and reception) implied in this type of documentary. For the dissertation corpus, we selected only the Brazilian feature documentaries exhibited in film festivals that had an impact in specialized criticism. The documentaries are: Diário de uma busca (Flávia Castro, 2010), Elena (Petra Costa, 2012), Mataram meu irmão (Cristiano Burlan, 2013) and Os dias com ele (Maria Clara Escobar, 2013). This research is theoretically based in the interdisciplinary perspective originated from the interface between communication and psychoanalysis. From the studies of documentary film in the communication area, we highlight the following themes: the documentary concept, the history of documentary, the family film, the use of archive image, alterity, ethics and aesthetics. From the psychoanalitic theory, concerning Sigmund Freud and Jacques Lacan’s paradigm, we approach the following concepts: subject, memory, fantasy, family romance, mourning, ethics, sublimation and relation between the subject and the image. In terms of methodology, the research is characterized as bibliographic research and as film analysis, presenting an investigation about narration, image, connections between image and sound and montage. In these Brazilian (auto)biographical documentaries, we watch a performing mode to narrate the story of the other who had gone. The documentary filmmaker’s subjectivity interferes decisively in this narrative which memory and fantasy interlace, resulting in an engaging narrative that has its own hybrid language. Therefore, these stories are no longer intimate and particular, they also become public and universal in a public-private-shared-collective metamorphic state of flux. The complexity of life is contemplated, when the borders of documentary advance on the limits of art and its creative possibilities